Sandy Materials in Civil Engineering Usage and Management - Nemati, Saeed; Tahmoorian, Farzaneh (IntechOpen, 2020)
As the world moves further into urbanization, there is a greater need for construction materials to meet society's needs. As natural resources become scarce, the use of recycled materials for construction purposes has become increasingly common. Over the past decade, there has been a significant increase in the utilization of recycled materials in the construction industry. This will result in substantial advantages in structure and infrastructure construction coupled with a reduction in the construction cost, as well as improving sustainability. However, significant development limitations and many relevant considerations must be addressed when using recycled materials in construction. This book introduces innovative and alternative construction materials used in civil engineering.